The synchronism of hand's movement in tennis serve - Ioanna, T.; Alexandros, M.; Pavlos, N.; Evagelos, T.; Georgios, D. (Journal of Biology of Exercise, 2013)
The purpose of this research is the recording of the hands' synchronism during serve, from the moment the ball leaves the athlete's hand until the moment it contacts the racket .From this survey, it is observed that the time of synchronization of the first serve is on average lower than the second, and with significant statistical difference (p < .05). Moreover, the first serve's success rate seems to be irrelevant to its time synchronization and the athletes' ranking. Nevertheless, the correlation of time synchronization between the first and second serve is noticeably high, concluding that the athletes who are first in ranking have a personal stable and correlated time, in both first and second serves.